1992
DOI: 10.1136/bmj.304.6841.1531
|View full text |Cite
|
Sign up to set email alerts
|

Sexual contact in the doctor-patient relationship in The Netherlands.

Abstract: Objective-To obtain data on sexual contact between doctors and their patients.Design-Anonymous questionnaire with 17 items sent to all working gynaecologists (n=595) and all ear, nose, and throat specialists (n=380) in the Netherlands.Results In 1984, Henderikx and Van Son-Schoones studied 75 male general practitioners, 75 social workers, and 75 female district nurses. Of the 39% (29) of general practitioners responding 21% (six) stated that they had had erotic physical contact with a patient, 3% (1) of whom h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In overseas surveys, 3%–10% of doctors admit to a sexual relationship with a patient. 5 ‐ 7 In Australia, an anonymous mail survey of psychiatrists found that 7.6%, almost all male, reported erotic contact with patients during or after termination of treatment. 8 Based on NSW Health Care Complaints Commission information, about 4% of male psychiatrists in NSW have been reported for sexual abuse of patients.…”
Section: Is There a Problem?mentioning
confidence: 99%
“…In overseas surveys, 3%–10% of doctors admit to a sexual relationship with a patient. 5 ‐ 7 In Australia, an anonymous mail survey of psychiatrists found that 7.6%, almost all male, reported erotic contact with patients during or after termination of treatment. 8 Based on NSW Health Care Complaints Commission information, about 4% of male psychiatrists in NSW have been reported for sexual abuse of patients.…”
Section: Is There a Problem?mentioning
confidence: 99%
“…Overseas research on sexual misconduct in health care settings has focused on medical practitioners and psychologists, with few studies of other health care professions . Our study is the first to examine sexual misconduct notifications for a national cohort of all registered health practitioners.…”
mentioning
confidence: 99%
“…Although mental health professionals have experienced negative attitudes or feelings in relation to their sexual attractions (Rodolfa et al, 1994; Wilbers et al, 1992), the SPCs reported low levels of emotional intensity with respect to their attractions regardless of their gender or degree area. The SPCs viewed their sexual attraction as neither harmful nor beneficial and thought that their client-athletes were unaware of their feelings, suggesting a potential naiveté regarding how attuned their client-athletes likely are to SPCs’ attractions and behaviors.…”
Section: Discussionmentioning
confidence: 99%